Representing Gender: Visual Literacy Instruction in the Academic Library - Fullmer Millicent (Open Information Science, 2019)
Contemporary society is dominated by visual communication, yet visual literacy is a learned skill that requires training. Gender issues, particularly the subjects of gender diversity and power struggles, are deeply pertinent to today’s visual culture. The critical consumption of information has long been taught in libraries, though instruction has typically prioritized text-based sources. However, visual literacy instruction has the capacity to provoke critical inquiry into issues of gender, race, social class, and ethnicity. As institutions that promote social justice, libraries can help improve diversity and inclusion in their communities through teaching visual literacy skills at all levels. Critical visual literacy instruction can also help academic libraries advance student scholarship, which can only be achieved if they are literate in all forms of knowledge production.